Harmony of Tradition and Innovation: A Distinctive Approach for Arabic Language Learning in Madrasah with Adab and Tahfidz Integration - Ahmadi Ahmadi; Nurhasma Muhamad Saad (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2024)
The integration of traditional Islamic values with innovative pedagogical approaches in Arabic language education, especially in contexts such as Madrasah Ibtidaiyah Muhammadiyah in Pacitan, is critical to improving learning outcomes. However, empirical studies are still rare to evaluate the effectiveness and sustainability of these approach, so in-depth research is needed to assess impacts, challenges and best practices. This approach emphasizes a perfect blend of Adab (Islamic etiquette) and Tahfidz (Qur’an memorization) programs in the Arabic curriculum, aiming to foster holistic development among students. This study explores in depth the theoretical foundations of this integrated approach, highlighting the symbiotic relationship between tradition and innovation in educational practice. Adab functions as a moral compass, guiding students toward ethical behavior and character refinement, while Tahfidz enhances cognitive abilities and linguistic proficiency. This research uses a qualitative descriptive method approach, which emphasizes research methodology to comprehensively assess the effectiveness of the proposed approach. Qualitative data collection methods include in-depth interviews, include surveys before and after implementation, assessment and evaluation of academic performance. Qualitative data analysis involves thematic coding and narrative synthesis. This study contributes to the development of Arabic language education discourse in Madrasas by proposing a transformative approach that aligns tradition with innovation.